Does Femoral Component Rotation Matter in Functionally Aligned Total Knee Arthroplasty? The Effect of Deviations From the Transepicondylar Axis on Patient-Reported Outcomes at 1 Year - Farey, John E.; Chew, Jordan; Wood, Jil A.; Chen, Darren B.; Macdessi, Samuel J. (The Journal of Knee Surgery, 2025)
Femoral component rotation (FCR) in total knee arthroplasty (TKA) is critical for flexion balance and patellofemoral tracking. Deviations from the transepicondylar axis (TEA) have been linked to poor outcomes. This study aimed to assess the impact of FCR on patient-reported outcomes in functionally aligned (FA) TKAs. A total of 448 robotic-assisted FA TKAs with preresection gap balancing were performed in 393 patients between June 1, 2018, and December 31, 2021. Demographic, radiographic, and patient-reported outcome measures (PROMs) were prospectively collected at baseline and 1 year postoperatively. FCR was set within a range of ± 6 degrees relative to the TEA as part of an FA TKA alignment strategy. The primary outcome was the relationship between final intraoperative FCR and PROMs at 1 year, including the Knee injury and Osteoarthritis Outcome Score-12 (KOOS-12) and the EuroQol 5-Dimension-5-Level (EQ5D-5L) score. Mean FCR was 0.0 degrees (SD ± 2.1 degrees, range: −5.8 to 7.0 degrees). At 1 year, KOOS-12 increased by a mean of 44.1 points (p < 0.01), and EQ5D-5L by 7.6 points (p < 0.01). No significant correlation was found between FCR and KOOS-12 (r = −0.09, p = 0.3). A weak negative correlation existed between increasing external FCR and EQ5D-5L (r = −0.12, p = 0.03). Categorizing FCR into internal (<-2 degrees), neutral (± 2 degrees), and external rotation (≥2 degrees) showed no significant differences in outcomes. FA TKA leads to significant improvements in PROMs, regardless of FCR within a functional range, at 1 year postoperatively. The study is a cross-sectional study providing Level III evidence.
Keywords: alignment; arthroplasty; femoral component rotation; functional alignment; robotic